2015
DOI: 10.3748/wjg.v21.i34.9863
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs and long non-coding RNAs in gastric cancer diagnosis: An update and review

Abstract: Gastric cancer (GC) is the fourth most common cancer and the third leading cause of cancer mortality worldwide. MicroRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are the most popular non-coding RNAs in cancer research. To date, the roles of miRNAs and lncRNAs have been extensively studied in GC, suggesting that miRNAs and lncRNAs represent a vital component of tumor biology. Furthermore, circulating miRNAs and lncRNAs are found to be dysregulated in patients with GC compared with healthy individuals. Circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 219 publications
1
78
0
1
Order By: Relevance
“…However, MT1JP expression was not associated with factors such as gender, age, alcohol consumption, smoking, tumor differentiation, location, venous invasion, local invasion and distant metastasis. Non-invasive approach using circulating lncRNAs provides new alternatives for cancer detection and prognosis evaluation [15,17,18]. Thus, we also measured MT1JP expression in plasma samples from 34 GC patients and paired healthy donors.…”
Section: Correlation Of Mt1jp Expression With Clinicopathological Feamentioning
confidence: 99%
See 2 more Smart Citations
“…However, MT1JP expression was not associated with factors such as gender, age, alcohol consumption, smoking, tumor differentiation, location, venous invasion, local invasion and distant metastasis. Non-invasive approach using circulating lncRNAs provides new alternatives for cancer detection and prognosis evaluation [15,17,18]. Thus, we also measured MT1JP expression in plasma samples from 34 GC patients and paired healthy donors.…”
Section: Correlation Of Mt1jp Expression With Clinicopathological Feamentioning
confidence: 99%
“…Mechanistically, lncRNAs may act as chromatin remodeler, transcriptional modulator, splicing regulator, posttranscriptional processor, enhancer, molecular decoys for miRNAs, or as a guide for protein-protein, protein-DNA and protein-RNA interaction [4,5,13,14]. Given the properties of disease-, tissue-and developmental-specificity, lncRNA may serve as a candidate biomarker for GC diagnosis [9,13,15]. Indeed, recent evidences have confirmed that several lncRNAs may not only provide significance for GC diagnosis, stage assessment and prognosis prediction, but also serve as promising targets for GC treatment [9,13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, besides the upregulated miRNAs, many circulating miRNAs are reduced in the blood of GC patients. miR-122 and miR-195 are the two mainly downregulated circulating miRNAs in GC patients, thus suggesting that both of them were potential diagnostic markers for GC screening [ 169 ].…”
Section: Gastric Cancermentioning
confidence: 99%
“…Mature miRNA binds to the 3'-untranslated (UTR) region of its target mRNA, forming silencing complexes and inducing the degradation of target mRNA or inhibiting its translation (13,14). miRNAs are stable molecules that may be developed as biomarkers for various diseases and their levels are high in the peripheral blood (15). In addition, miRNAs are involved in almost all pathological and physiological processes in eukaryotic cells, including cancer, cardiovascular disease, Alzheimer's disease and inflammation (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%